Analisis Studi Kelayakan Bisnis untuk Pengembangan Usaha Kuliner Berbasis Lokal - Siti Nurkomalasari; Rasika; Dwi Astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Business feasibility studies play an important role in determining the success of locally based culinary businesses. This article analyzes market, technical, financial, legal and social aspects that influence the development of local culinary businesses. Data was collected through survey methods, interviews with business actors, and literature studies. The research results show that the success of locally based culinary businesses is greatly influenced by product uniqueness, digital marketing strategies and operational sustainability.